Deciphering structure and aggregation in asphaltenes: hypothesis-driven design and development of synthetic model compounds - Scott, David E.; Schulze, Matthias; Stryker, Jeffrey M.; Tykwinski, Rik R. (Chemical Society Reviews, 2021)
Asphaltenes comprise the heaviest and least understood fraction of crude petroleum. The asphaltenes are a diverse and complex mixture of organic and organometallic molecules in which most of the molecular constituents are tightly aggregated into more complicated suprastructures. The bulk properties of asphaltenes arise from a broad range of polycyclic aromatics, heteroatoms, and polar functional groups. Despite much analytical effort, the precise molecular architectures of the material remain unresolved. To understand asphaltene characteristics and reactivity, the field has turned to synthetic model compounds that mirror asphaltene structure, aggregation behavior, and thermal chemistry, including the nucleation of coke. Historically, molecular asphaltene modeling was limited to commercial compounds, offering little illumination and few opportunities for hypothesis-driven research. More recently, however, rational molecular design and modern organic synthesis have started to impact this area. This review provides an overview of commercially available model compounds but is principally focused on the design and synthesis of structurally advanced and appropriately functionalized compounds to mimic the physical and chemical behavior of asphaltenes. Efforts to model asphaltene aggregation are briefly discussed, and a prognosis for the field is offered. A referenced tabulation of the synthetic compounds reported to date is provided.
CRIS-Team WoS Importer:2021-07-16

Steroid-Derived Naphthoquinoline Asphaltene Model Compounds: Hydriodic Acid Is the Active Catalyst in I-2-Promoted Multicomponent Cyclocondensation Reactions - Schulze, Matthias; Scott, David E.; Scherer, Alexander; Hampel, Frank; Hamilton, Robin J.; Gray, Murray R.; Tykwinski, Rik; Stryker, Jeffrey M. (Organic Letters, 2015)
A multicomponent cydocondensation reaction between 2-aminoanthracene, aromatic aldehydes, and 5-alpha-cholestan-3-one has been used to synthesize model asphaltene compounds. The active catalyst for this reaction has been identified as hydriodic acid, which is formed in situ from the reaction of iodine with water, while iodine is not a catalyst under anhydrous conditions. The products, which contain a tetrahydro[4]helicene moiety, are optically active, and the stereochemical characteristics have been examined by VT-NMR and VT-CD spectroscopies, as well as X-ray crystallography.

Synthesis and Aggregation Behavior of Chiral Naphthoquinoline Petroporphyrin Asphaltene Model Compounds - Schulze, Matthias; Scherer, Alexander; Hampel, Frank; Stryker, Jeffrey M.; Tykwinski, Rik (Chemistry - A European Journal, 2016)
The synthesis of structurally relevant compounds that model the chemical behavior and supramolecular aggregation of the asphaltenes, the most polar and metal-rich fraction of heavy petroleum, has been extended to include fusions of important petroleum biomarkers. The synthetic protocol features a multicomponent reaction to form a dyad composed of a fused steroidal naphthoquinoline, followed by a pyrrole cyclocondensation reaction to incorporate the dyad into a chiral triad containing a Ni-porphyrin substituent. This synthetic protocol has been used to prepare large molecules that represent both "continental" and "archipelago" models of asphaltene composition. The steroid-naphthoquinoline-porphyrin triads have been studied by UV/Vis and circular dichroism (CD) spectroscopies, and the results suggest that the naphthoquinoline core, a tetrahydro[4]helicene, adopts a helical conformation, producing a CD signal electronically related to the characteristic Soret absorption band of the porphyrin subunit. Finally, supramolecular aspects of asphaltene aggregation have been examined on a molecular level through analysis of axial coordination of pyridine to the Ni-porphyrin. The relative affinity of pyridine for binding to the Ni center of the porphyrin is evaluated by comparing binding propensities in a series of sterically differentiated substituted porphyrins.
Keywords: cracking; multicomponent reaction; porphyrinoids; steroids; supramolecular chemistry

Unexpected Michael Additions on the Way to 2.3,8.9-Dibenzanthanthrenes with Interesting Structural Properties - Reus, Christian; Lechner, Marc; Schulze, Matthias; Lungerich, Dominik; Diner, Colin; Gruber, Marco; Stryker, Jeffrey M.; Hampel, Frank; Jux, Norbert; Tykwinski, Rik (Chemistry - A European Journal, 2016)
The synthesis and properties of a new polycyclic aromatic hydrocarbon containing eight annulated rings and based on the anthanthrene core is described. An unexpected, nucleophile-dependent Michael addition to a dibenzanthanthrene-1,7-dione is found, giving a product with three triisopropylsilylacetylene units and a remarkable solid-state structure (as determined by X-ray crystallography).
EAM Import::2019-03-12